The relationship between eating disorder symptoms and obsessive compulsive disorder in primigravida women - Soheila Mohamadirizi; Masoumeh Kordi; Mohamad Taghi Shakeri; Morteza Modares-Gharavi (Wolters Kluwer Medknow Publications, 2015)
Background: Eating Disorder Symptoms are among the most common disorders in perinatal period and are influenced by various environmental and psychosocial factors such as anxiety disorders. So, the aim of this study was to determine the relationship between Eating Disorder symptoms and Obsessive Compulsive disorder in primigravida women. Materials and Methods: This cross-sectional study was carried on 213 in primigravida women referring to Mashhad health care centers, selected through a two stage sampling method (cluster-convenience) in Mashhad in 2013. Demographic and prenatal characteristics Questionnaire, Eating Disorder Examination Questionnaire (EDE-Q)(26Q) and Maudsley Obsessive Compulsive Questionnaire (30Q) were completed by the subjects. The statistical analysis was performed with various statistical tests such as Pearson correlation coefficient, t-test, one-way ANOVA and linear regression. Significance level was considered as P < 0.05. Results: Based on the findings 94.6% of the subjects had Obsessive Compulsive disorder, and 18% had Eating Disorder Symptoms. In addition, there was a poor positive correlation between the rate of Eating Disorder Symptoms and Obsessive Compulsive. Conclusions: There was a correlation between the Eating Disorder Symptoms and Obsessive Compulsive in pregnant women. It is recommended to eliminate or decrease Eating Disorder Symptoms and Obsessive Compulsive among Iranian pregnant women through preventive measures.